Lipoxygenase Inhibition by Plant Extracts - Melita Lončarić; Ivica Strelec; Tihomir Moslavac; Drago Šubarić; Valentina Pavić; Maja Molnar (Biomolecules, 2021)
Lipoxygenases are widespread enzymes that catalyze oxidation of polyunsaturated fatty acids (linoleic, linolenic, and arachidonic acid) to produce hydroperoxides. Lipoxygenase reactions can be desirable, but also lipoxygenases can react in undesirable ways. Most of the products of lipoxygenase reactions are aromatic compounds that can affect food properties, especially during long-term storage. Lipoxygenase action on unsaturated fatty acids could result in off-flavor/off-odor development, causing food spoilage. In addition, lipoxygenases are present in the human body and play an important role in stimulation of inflammatory reactions. Inflammation is linked to many diseases, such as cancer, stroke, and cardiovascular and neurodegenerative diseases. This review summarized recent research on plant families and species that can inhibit lipoxygenase activity.